Enhanced mnemonic discrimination for emotional memories: the role of arousal in interference resolution. - Szőllősi, Ágnes; Racsmány, Mihály (Memory & Cognition, 2020)
In the present study we investigated the long-standing question whether and why emotionally arousing memories are more distinct as compared to neutral experiences. We assumed that memory benefits from the distinctiveness of emotional information, and that emotions affect encoding by reducing interference among overlapping memory representations. Since pattern separation is the process which minimizes interference between memory representations with similar features, we examined the behavioral manifestation of putative neural mechanisms enabling pattern separation (i.e. mnemonic discrimination) for emotionally arousing materials using the Mnemonic Similarity Task with negative, positive, and neutral images as stimuli. Immediately after incidental encoding, subjects were presented with stimuli they had seen at encoding and also with new items. Crucially, participants were also presented with lure images that were visually similar to ones they had seen before. Response options were old, new, and similar. Our results showed that individuals were better in discriminating between similar, emotionally arousing memories, when compared to the neutral stimuli. Moreover, this so-called lure discrimination performance was better for the negative images, than it was for the positive stimuli. Finally, we showed that the high arousing negative stimuli were better separated than the low arousing negative stimuli, and a similar pattern of results was found for the positive items. Altogether, these findings suggest that lure discrimination is modulated by arousal and not by valence. We argue that noradrenergic activity might facilitate interference resolution among memory representations with similar features, and that superior pattern separation might play a key role in memory enhancement for emotional experiences.